1999
DOI: 10.1007/s004310051026
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary dysfunction, morbidity and mortality with congenital midline malformation of the cerebrum

Abstract: Children with congenital midline brain defects frequently manifest convulsions, neurodevelopmental disability and poor growth due to disordered metabolism and/or neuro-anatomy. Treating clinicians must be aware of the complex, dynamic neurological and metabolic nature of these patients and their potential for early demise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
46
2
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(51 citation statements)
references
References 23 publications
2
46
2
1
Order By: Relevance
“…Anterior pituitary dysfunctions such as growth hormone deficiency, central hypothyroidism, and hypocortisolism were previously observed, and diabetes insipidus was also identified as a common problem. Endocrinopathies were evident in 28.6% of the surviving patients in this study, which is lower than in the results of a study that reported a prevalence of 59% [28]. This finding may be attributable to the relatively shorter period of observation and higher ratio of milder holoprosencephaly types than was described in the study mentioned above [28].…”
Section: Discussioncontrasting
confidence: 81%
“…Anterior pituitary dysfunctions such as growth hormone deficiency, central hypothyroidism, and hypocortisolism were previously observed, and diabetes insipidus was also identified as a common problem. Endocrinopathies were evident in 28.6% of the surviving patients in this study, which is lower than in the results of a study that reported a prevalence of 59% [28]. This finding may be attributable to the relatively shorter period of observation and higher ratio of milder holoprosencephaly types than was described in the study mentioned above [28].…”
Section: Discussioncontrasting
confidence: 81%
“…Pituitary hypoplasia manifests itself in different degrees of hormone deficiency, from a single hormone deficit to panhypopituitarism 4,5,7,11,19,24,25 . The deficiencies also can evolve gradually over time 7,18,25 .…”
Section: Pituitary Hormone Deficiencymentioning
confidence: 99%
“…The deficiencies also can evolve gradually over time 7,18,25 . Growth hormone (GH) deficiency is the most common, followed by adrenocorticotropic hormone (ACTH) and tireotrophic hormone (TSH) deficiencies 21,24 . Gonadotrophic function is generally preserved 26 and diabetes insipidus is found more rarely 5,26 .…”
Section: Pituitary Hormone Deficiencymentioning
confidence: 99%
See 2 more Smart Citations